Meat reduction, vegetarianism, or chicken avoidance: US omnivores' impressions of three meat-restricted diets. Issue 1 (18th September 2020) - Asher, Kathryn E.; Peters, Paul
Abstract : Purpose: Meat consumption has a variety of implications in society. While various types of meat-restricted diets exist to address this, not enough is known about how the average meat consumer views different avenues to lessening their intake. In response, this study aims to assess US omnivores' impressions of three meat-restricted diets. Design/methodology/approach: An online survey was administered to a cross-sectional, census-balanced sample from Nielsen of 30, 000+ US adults. Omnivores ( N = 928) were randomized into one of the three conditions where they were asked about their perceptions of a vegetarian diet, a reduced-meat diet or a chicken-free diet as individuals not currently following that dietary pattern. Findings: The findings showed that omnivores had a more favorable perception of a reduced-meat diet on a greater number of study variables as compared to the vegetarian or chicken-free diets. The research also demonstrated that a majority of omnivores were in the precontemplation stage of cognitive change, suggesting that most American omnivores are not actively demonstrating a readiness to alter their meat consumption in the ways presented. Originality/value: This research is the first to examine the comparative trends around these three diets among omnivores. It also speaks to how the desirability of meat restriction varies by type of approach, i.e. elimination or reduction, and if the latter, what type. The findings may be of relevance for efforts to reduce global meat consumption for ethical, health, or environmental reasons.